Keynes and Economic Analysis Today - Angell, James W. (The Review of Economics and Statistics, 1948)
LORD KEYNES died just ten years after publication of his great book, at very peak of his professional and public career. Both his death, and simultaneous conclusion of first Keynesian decade, make preparation of two volumes, here reviewed,' timely and a fitting tribute. No one man in history of economics had so great an effect upon minds and daily lives of so many people in so short a time as did Keynes. Although students have disagreed to a remarkable extent about which one of several possibilities is the crucial feature of Keynesian Revolution, and although Keynes operated in only certain fields of economics, reality of revolution itself is beyond discussion'. Both science and art of economics, at least within capitalist societies, have been permanently changed and one can only say enormously advanced by his work. With respect to major analytical concepts which Keynes developed or reformulated, it is almost as pointless to talk today of pro-Keynesians and anti-Keynesians as to say that particular individuals are for or against multiplication table. The shapes and values to be assigned to particular relations, such as that of consumption to income; particular analytical conclusions drawn, such as that concerning underemployment equilibrium; and above all resulting policy proposals, such as those concerning government deficit spending these are another matter, and have precipitated tremendous amounts of discussion. But very discussions themselves have been largely couched in Keynes' own terms, have been centered around his particular conceptions and formulations of problems in issue, and in their whole character have differed in remarkable degree from those of preceding periods. Dr. Klein's book is in main a restatement and defense of Keynes' ideas, done with almost religious enthusiasm but nonetheless on a high level of scholarship. I have already tried parts of it in a graduate class, and found it extremely useful. It covers, if not always systematically, whole range of Keynes' ideas on monetary and general economic analysis from his earliest writings, and touches on much of relevant work of others. Perhaps most illuminating sections are chapter on Keynes as a classical economist, especially sections on Treatise; summary of argument of General Theory; and technical Appendix. The first of these undertakes, and with great success, to build a continuous bridge of ideas from older forms of monetary theory to equations of Treatise, to explain each stage in terms of what had gone before, and to lead into foundations of General Theory. The Treatise equations are described as pretentious, and Hansen's criticism is of course admitted, but, it is argued (I think correctly) that they are not essential contribution of Treatise, and that their defects do not impair determinacy of prices in system which was here Keynes' main goal (pp. I 7, 24, and Appendix). The Appendix is especially interesting for its examination of Pigou's attempt to rehabilitate classical doctrine, at least for problems of long-run equilibrium. The other chapters consist in main of a relatively brief but excellent re-presentation of essential analytical argument of General Theory, largely as systematized and expanded by Keynes' followers (little is said of confusions and contradictions of General Theory itself!), and a series of reviews of certain of main controversies. Despite Dr. Klein's almost excessive zeal in defending Keynes at some points (cf. p. I 54), and despite a certain lack of integration and order (surely Chapter V is misplaced?), book is an important addition to literature because, though hardly exhaustive, it brings much of analytical content of Keynesian discussions together in a compact ' Seymour E. Harris, editor, The New Economics (New York, I947); Lawrence R. Klein, The Keynesian Revolution (New York, I947).